Isolation and identification of soil fungi isolates from forest soil for flooded soil recovery - Nor Hazwani, Aziz; N., Zainol (IOP Publishing Ltd, 2018)
Soil fungi have been evaluated for their ability in increasing and recovering nitrogen, phosphorus and potassium content in flooded soil and in promoting the growth of the host plant. Host plant was cultivated in a mixture of fertile forest soil (nutrient-rich soil) and simulated flooded soil (nutrient-poor soil) in an optimized soil condition for two weeks. The soil sample was harvested every day until two weeks of planting and was tested for nitrogen, phosphorus and potassium concentration. Soil fungi were isolated by using dilution plating technique and was identified by Biolog's Microbial Systems. The concentration of nitrogen, phosphorus, and potassium was found to be increasing after two weeks by two to three times approximately from the initial concentration recorded. Two fungi species were identified with probability more than 90% namely Aspergillus aculeatus and Paecilomyces lilacinus. Both identified fungi were found to be beneficial in enhancing plant growth and increasing the availability of nutrient content in the soil and thus recovering the nutrient content in the flooded soil.